Certain Classes of Fuzzy Graphs (European Journal of Pure and Applied Mathematics, 2017)
In this paper, several classes of fuzzy graphs are characterized and we provide two new operations on fuzzy graphs; namely parallel connection and series connection. We show that parallel connection and series connection of balanced fuzzy graphs need not be balanced and they are balanced in case the original graphs are induced by cycles. Finally, we study the notions of strong and complete via these operations.